Primary insomnia patients' performances during simulated car following and urban driving in the afternoon. (31st March 2019) - Perrier, Joy; Amato, Jean‐Noël; Berthelon, Catherine; Bocca, Marie‐Laure
Abstract: According to epidemiological studies, insomnia is associated with an increase in risk of traffic accidents. Recent investigations revealed that patients with insomnia had driving performance impairment under monotonous conditions. However, it is unclear whether other driving abilities may be impacted by insomnia, especially those needing more attentional resources than those involved in monotonous driving. Other findings revealed that impaired performances are more likely to occur with the increase of cognitive demands. However, such tests did not reflect difficulties in situations of everyday life expressed by patients with insomnia, such as driving in an urban environment with traffic and critical situations. Therefore, behaviour in situations encountered in everyday life has to be explored. The aim of the present study was to assess driving performances of patients with insomnia in daily routine tasks such as urban and car‐following tests. For this purpose, 15 patients with insomnia and 16 good sleepers performed an urban test of driving with original risk scenarios and a car‐following test during the middle afternoon. No significant behavioural difference between patients with insomnia and good sleepers has been found in both the urban test and the car‐following test, showing that patients with insomnia have no impairment in behaviour implicated in daily contexts driving tasks of short period of time performed in the late afternoon. Although our results provide a first step towards knowledge of behavioural performance during daily routine driving tasks in patients with insomnia, future studies are needed using on‐the‐road driving tests and/or different population of patients with insomnia before generalisation.